Comparative Effects of Think Pair Share and Think Pair Square on Critical Thinking in Qur'an-Hadith Education: The Role of Prior Islamic Schooling Background - Salsabila Mustopa; Tryana Hafilda; Wati Susilawati; Adam Malik; Andewi Suhartini (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2026)
Critical thinking is an essential competency in Islamic education, particularly in Qur'an-Hadith learning, as it supports students in interpreting religious texts reflectively and analytically. However, limited empirical studies have compared cooperative learning models while considering students’ diverse prior educational backgrounds. This study aimed to examine the effects of Think Pair Share (TPS), Think Pair Square (TPSq), and conventional instruction on students’ critical thinking skills, as well as the influence of prior educational backgrounds, including SMP, MTs, and Diniyah pesantren. A quantitative quasi-experimental design with a 3 × 3 factorial arrangement was applied to 62 eleventh-grade students from three intact classes at SMA Negeri 1 Kalijati. Critical thinking was measured using a validated 30-item instrument based on Ennis’s framework (α = 0.899), and data were analyzed using two-way ANOVA and Bonferroni tests. The results showed that instructional model significantly affected critical thinking, with TPSq yielding the highest mean score, followed by TPS and conventional instruction. Prior educational background also had a significant effect, with Diniyah pesantren students outperforming MTs and SMP students. However, no interaction effect was found, indicating that TPSq was consistently effective across all groups. These findings contribute to Islamic education by demonstrating that structured cooperative learning enhances critical thinking in Qur'an-Hadith instruction regardless of students’ prior educational experiences.